1990
DOI: 10.1037/0097-7403.16.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Selective associations in the observational conditioning of fear in rhesus monkeys.

Abstract: Three experiments explored the issue of selective associations in the observational conditioning of fear. Experiment 1 results indicated that observer rhesus monkeys acquired a fear of snakes through watching videotapes of model monkeys behaving fearfully with snakes. In Experiment 2, observers watched edited videotapes that showed models reacting either fearfully to toy snakes and nonfearfully to artificial flowers (SN+/FL-) or vice versa (FL+/SN-). SN+/FL-observers acquired a fear of snakes but not of flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
4
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 91 publications
(101 reference statements)
9
117
4
2
Order By: Relevance
“…These systems are relatively independent from each other and there is often little correlation between measures of each index. The current study used self-report measures, whereas monkey (Cook & Mineka, 1989, 1990) and toddler (Dubi et al, 2008) studies have usually observed fear-related behaviour, and human conditioning studies have typically used physiological responses or self-report (e.g. Öhman & Soares, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These systems are relatively independent from each other and there is often little correlation between measures of each index. The current study used self-report measures, whereas monkey (Cook & Mineka, 1989, 1990) and toddler (Dubi et al, 2008) studies have usually observed fear-related behaviour, and human conditioning studies have typically used physiological responses or self-report (e.g. Öhman & Soares, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from fear-relevance, other characteristics of the CS may affect comparisons with studies such as those with monkeys (Cook & Mineka, 1989, 1990. Fear for stimuli is associated with perceptions of speediness and suddenness of movement (Bennett-Levy & Marteau, 1984) and young children show a predisposition to associate frightened voices with films of moving snakes, but not with still images of snakes (DeLoache & LoBue, 2009).…”
Section: Vicarious Learning Of Fear In Childhood 24mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there are probably more snake phobics among us than automobile phobics in spite of the fact that more people are killed by automobiles than snakes. (See M. Cook & Mineka, 1990, for work showing a built-in propensity for fear of snakes among rhesus monkeys.) My own position is not that extreme.…”
Section: Genetic Basis Of Attitudesmentioning
confidence: 99%